(untitled) (Maslahah: Journal of Islamic Studies, 2023)
The relationship between Dzul Khuwaishirah and the people who carried out the rebellion against Uthman, and the Khawarij who rebelled against Ali bin Abi Talib because of the At-Tahkim incident, is indeed very clear and visible. However, the term Khawarij is only appropriate for people who rebel against Ali bin Abi Talib because of the At-Tahkim incident, on the grounds that they exist as a group of people who form a group that has a political orientation and separate views that have had an influence on the matter of thought and belief in real terms, the opposite of the previous circumstances.